Development of problem-based learning digital teaching materials using heyzine flipbooks for the matrix topic - Karindi, Dito Risky; Rufi'i; Rachmadtullah, Reza (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2025)
The problem addressed in this study is the persistence of teacher-centered learning and the limited innovation in developing digital teaching materials, which has resulted in students’ low comprehension of mathematical concepts. This study aimed to develop digital teaching materials in the form of Heyzine Flipbooks using the Problem-Based Learning (PBL) model on the topic of matrices to improve students’ conceptual understanding, while also meeting the criteria of feasibility and practicality. The research employed the ADDIE development model. Expert validators consisted of media experts, material experts, and design experts, while user trials involved mathematics teachers and Grade XI students at SMAN 8 Surabaya. Data were collected through expert validation sheets, as well as teacher and student response questionnaires. The results showed that media experts gave an average validation score of 3.98, material experts 3.98, and design experts 3.50, all categorized as very feasible. In addition, practicality scores were 3.96 from teacher responses and 3.86 from student responses, both categorized as very practical. These findings indicate that the developed teaching materials are feasible and practical to enhance students’ conceptual understanding of mathematics.